ADDED-ROW GROWTH OF THE (2X1)O-CU(110) RECONSTRUCTION - Fauster, Thomas; et al. (Physical Review B, 1991)
By impact-collision ion-scattering spectroscopy we show that the growth of the (2 x 1)O reconstruction on Cu(110) proceeds via added Cu-O rows in the [001] direction on top of flat terraces. The observed small creation energy for copper adatoms provides a solution of the mass-transport problem in surface reconstruction. The Cu-O rows are formed by a condensation of adsorbed oxygen atoms and copper adatoms diffusing across the surface.